DRAMALEÃO: AFETOS DE UM CAMALEÃO PERANTE O DRAMA ATRAVÉS DA AMBIENTAÇÃO CÊNICA - Vanessa Lopes Ribeiro (2023)
This dissertation is a poetic account of a process that addresses the praxis of a drama with a pedagogical focus on the use of the scenic setting strategy for effectiveness in the teaching-learning process in theater teaching. The drama in question was applied in the fifth year of elementary school I, at Escola Municipal Arthur Campos Mello, located in the city of Dourados/MS, during the second half of 2022 and started from the pre-text “The little match-seller” (1848), by Hans Christian Andersen. In all episodes, the scenic setting is verticalized during the drama process and finds correlations with theatricality, providing the occurrence of immersion and experience in the process. The concepts of action, space and place, and their intersections with scenic setting and theatricality are concepts explored in this research. To support the discussion and analysis presented, authors such as Biange Cabral, Wellington Paula, Ariane Barros, Tharyn Freitas, Jorge Bondía and Josette Féral are used. Keyword: Scenic Environment; Theatricality; Process Drama; Theater-education.